"Winga Is Trying to Get in": Local Observations of Climate Change in the Tiwi Islands. Issue 3 (14th March 2023) - Barnett, Jon; Konlechner, Teresa; Waters, Elissa; Minnapinni, Michelle Woody; Jarillo, Sergio; Austral, Brian; De Santis, James; Head, Lesley; Rioli, Clinton; King, Andrew
Abstract: There is a growing body of research documenting Indigenous Peoples and Local Communities' observations of changes in climate. The accuracy, efficacy, and transferability of this research depends on its motives and methods. In this paper, we report on research to produce a working knowledge of changes in climate and its impacts on local biophysical systems in the Tiwi Islands in Northern Australia. Interviews with 52 Tiwi people were combined with diverse forms of aerial data to produce a nuanced understanding of climate change in these remote islands. These data show changes in climate‐sensitive biophysical systems that would otherwise remain undetected by instruments conventionally used for monitoring climate change. These include changes in shorelines, which are causing concerns about damage to buildings that are important for Tiwi well‐being, and changes in the marine environment and wetlands, which are causing concerns about damage to natural heritage. We discuss the implications of these findings, arguing that systematic observations collected by networks of people "on Country" can provide excellent monitoring of climate change impacts, and that Indigenous people's interests in the effects of climate change overlap with those of non‐Indigenous people, as do their rights to support from the State for adaptation. Plain Language Summary: Research that documents Indigenous and local people's observations of changes in the environment is essential to understand the broader implications of climate change. The observations reported in this study in the Tiwi Islands (Northern Territory, Australia) show environmental changes that would otherwise remain undetected by instruments conventionally used for monitoring climate change, particularly changes that affect crucial infrastructure, as well as changes in the marine and coastal environment. Tiwi Islanders observations help monitoring climate change impacts while reaffirming the rights of Indigenous peoples to get support for climate change adaptation from the State. Key Points: Tiwi people observe nuanced changes in the environment that are significant to them, and for understanding the impacts of climate change Tiwi people express concern about the risks of coastal erosion to buildings that are important for their daily lives and livelihoods Indigenous people's interests in adaptation overlap with those of non‐Indigenous people, as do their rights to support for adaptation